Comparative Study of Skeletal Stability between Postoperative Skeletal Intermaxillary Fixation and No Skeletal Fixation after Bilateral Sagittal Split Ramus Osteotomy: an 18 Months Retrospective Study - Jens Hartlev; Erik Godtfredsen; Niels Trolle Andersen; Thomas Jensen (Stilus Optimus, 2014)
Objectives: The purpose of the present study was to evaluate skeletal stability after mandibular advancement with bilateral sagittal split osteotomy. Material and Methods: Twenty-six patients underwent single-jaw bilateral sagittal split osteotomy (BSSO) to correct skeletal Class II malocclusion. One group (n = 13) were treated postoperatively with skeletal elastic intermaxillary fixation (IMF) while the other group (n = 13) where threated without skeletal elastic IMF. Results: The mean advancement at B-point and Pog in the skeletal elastic IMF group was 6.44 mm and 7.22 mm, respectively. Relapse at follow-up at B-point was -0.74 mm and -0.29 mm at Pog. The mean advancement at B-point and Pog in the no skeletal elastic IMF group was 6.30 mm and 6.45 mm, respectively. Relapse at follow-up at B-point was -0.97 mm and -0.86 mm at Pog. There was no statistical significant (P > 0.05) difference between the skeletal IMF group and the no skeletal group regarding advancement nor relapse at B-point or Pog. Conclusions: Bilateral sagittal split osteotomy is characterized as a stable treatment to correct Class II malocclusion. This study demonstrated no difference of relapse between the skeletal intermaxillary fixation group and the no skeletal intermaxillary fixation group. Because of selection-bias and the reduced number of patients it still remains inconclusive whether to recommend skeletal intermaxillary fixation or not in the prevention of relapse after mandibular advancement.